Design Improvement Of Packaging Of Kerupuk Strawberry Ukm Kencana Mas Using Quality Function Deployment - Reza Gilang Pramono; Muhammad Iqbal; Sari Wulandari (eProceedings of Engineering, 2015)
UKM Kencana Mas is a Small Medium Enterprise (SME) consist of female farmers and housewives who produce a wide variety of snacks and foods. One of the most popular product of UKM Kencana Mas is Kerupuk Strawberry, crunchy cracker made from strawberry. UKM Kencana Mas wants to expand market and sell Kerupuk Strawberry to supermarkets. However, the company cannot do it because the packaging of the product has not been standardized yet. Therefore, UKM Kencana Mas should improve the packaging of the product so that it could attract more customer and can be sold at supermarkets. This research aimed to give recommendation of improved packaging design of Kerupuk Strawberry using Quality Function Deployment (QFD) method. The choice of QFD was because it is a customer-oriented method which will improve customers’ satisfaction. The research was conducted by interviewing customers, collecting Voice of Customers (VoC), spreading questionnaire, computing Gap, determining technical characteristics, creating House of Quality (HoQ) matrix, developing concepts, determining critical part, creating part depolyment matrix, and create visual prototype. The recommendations of packaging design are using combination of pink and red color, shaped standing pouch, using material made from aluminum foil, showing picture of product and strawberry, using BetyBerry brand, using combination mark logo, placing the information on the back side of the packaging, and using font Showcard Gothic for the brand, and Arial for product information. Keyword— Design, Packaging, Quality Function Deployment, QFD